Extracellular polymeric substances from Spirulina sp. for the bioremediation of fishing net–derived microplastics in seawater - Sri Hapsari Wahyuningtyas; Adian Khoironi; Lilibeth Bucol (Journal of Emerging Science and Engineering, 2026)
The increasing accumulation of plastic waste from fishing nets is primarily driven by the large volume of nets introduced into aquatic systems. Fishing nets are predominantly manufactured from polyethylene, a polymer known for its high resistance to degradation, allowing it to persist in marine environments for hundreds of years. Consequently, discarded or degraded fishing nets represent an ongoing environmental challenge, which is further exacerbated by their fragmentation into microplastics. In response to this issue, this study aims to evaluate the effectiveness of extracellular polymeric substances (EPS) produced by Spirulina sp. for the bioremediation of polyethylene-derived microplastics from fishing nets in seawater. A quasi-experimental design was employed, consisting of control and treatment reactors. EPS was applied at concentrations of 20, 30, and 40 mg in the treatment reactors, while the control reactor received no EPS addition. The remediation process was conducted over treatment periods of 5, 9, and 13 days. Following the treatment, laboratory analyses were performed to assess changes in key water quality parameters, including salinity, dissolved oxygen (DO), pH, total dissolved solids (TDS), chemical oxygen demand (COD), and Spirulina growth rate. In addition, the residual microplastics that were not flocculated were quantified. The results indicated that the presence of microplastics influenced the growth dynamics of Spirulina. Nevertheless, EPS application resulted in a measurable reduction in microplastic mass, with decreases of 5.0 g, 10.1 mg, and 11.6 mg observed in the 20, 30, and 40 mg treatments, respectively. Overall, the findings demonstrate that bioremediation using Spirulina-derived EPS is effective in reducing polyethylene microplastics in seawater. Future studies are recommended to extend the treatment duration, utilize natural seawater under environmentally realistic conditions, and evaluate the broader ecological impacts of EPS-based bioremediation to support its practical application in marine environments.